EFFECT OF WORK ENVIRONMENT AND WORK COMPETENCY ON PERFORMANCE OF KPPU EMPLOYEES WITH WORK DISCIPLINE AS INTERVENING VARIABLE - Widodo, Arif Bagus; Djamil, Masyhudzulhak; Badawi Saluy , Ahmad (Dinasti International Journal of Digital Business Management, 2021)
The background of the research in this thesis is that an agency often only demands high performance from employees, regardless of the factors that influence it, even though the fundamental factors in supporting performance, such as competence, work discipline and work environment must also be considered for the sake of increasing employee productivity. The research questions in writing this thesis are: (1) How does the work environment affect the work discipline of KPPU's employees (2) How is the influence of the Work Environment on KPPU Employee Performance? (3) How does competence affect KPPU's employees' work discipline? (4) How does competence affect KPPU's employee performance? (5) How does work discipline affect KPPU' s employee performance? (6) What is the indirect effect of the Work Environment on KPPU Employee Performance through Work Discipline? (7) What is the indirect effect of Work Competence on KPPU Employee Performance through Work Discipline. This type of research is a causal research which aims to test the hypothesis about the effect of the independent variables (work environment, competence and work discipline) on the dependent variable (employee performance) in the Business Competition Supervisory Commission. From the results of this study, the authors concluded that: (1) Work Environment affects Work Discipline. (2) The work environment affects employee performance. (3) Competence affects work discipline. (4) Competence affects employee performance. (5) Work Discipline affects Employee Performance. (7) The work environment has an indirect effect on employee performance through work discipline. (8) Competence has an indirect effect on Employee Performance through Work discipline.